La zone canadienne des 200 milles dans l’Atlantique, un exemple de la nouvelle géographie politique des océans - Sanguin, André-Louis (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1980)
Following upon the Third Conference on the Law of the Sea begun in 1973, the principal maritime States of the world assumed exclusive national jurisdiction over a 12- mile zone extending from their coastlines and a 188-mile economic zone beyond territorial waters. Together they constitute the more familiarly referred to « 200-mile zone ». This new practice radically changed the political geography of the oceans, lessened the area within which the freedom of the seas exists, diminished by more than a third the surface area of the high seas and dealt a heavy blow to the fishing xpeditions of foreign trawlers. Canada is one of the principal users and one of the most vigourous defenders of the 200-mile principle for geographical reasons as much as for economic or political ones. The excessive exploitation of the seabed has been felt to be a threat for a portion of the population of the Eastern part of Canada. A firm policy criticized for being somewhat unilateral has enabled Canada to eliminate foreign fleets from its 200-mile zone. Over a period of 30 years the International Commission for North-West Atlantic Fisheries (ICNAF) attempted to introduce a positive international cooperation in order to eliminate the anarchic excessive exploitation. It was replaced in 1979 by the North-West Atlantic Fisheries Organization. A major dispute exists between France and Canada with respect to the delimitation of the economic zone of Saint-Pierre and Miquelon, French land since 1604. More generally, the question is posed as to how long the 200-mile principle will prevail in this new political geography of the oceans.